Tinjauan ilmiah dan Islam terhadap Terapi Murottal: Studi Komparatif antara Perspektif Medis dan Al-Qur’an - Permadani, Aditia Dwi; Selena, Nikki; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
Mental and physiological health are two essential and interrelated aspects of human life. As non-pharmacological therapy methods continue to develop, listening to Qur’anic recitation has emerged as an effective alternative therapy for maintaining mental and physical balance. The Qur’an’s recitation, rich in meaning, rhythm, and harmony, provides a relaxing effect that helps reduce anxiety, stress, and depression, while enhancing focus and promoting a positive mood through the stimulation of endorphin release and brainwave activity. From a physiological perspective, listening to the Qur’an has been shown to lower blood pressure in individuals with hypertension, stabilize heart rate, improve sleep quality, and support the function of the nervous and hormonal systems. This paper employs a descriptive qualitative method, not based on empirical field research, but through literature review and conceptual analysis from scientific and Islamic perspectives. The main issue discussed is how listening to Qur’anic recitation affects mental and physiological health, and how its effectiveness compares to other forms of auditory therapy. The proposed solution is by explaining how murottal stimulates relaxation and bodily balance while reinforcing spiritual values that secular therapies lack. Therefore, Qur’anic recitation therapy represents a holistic approach that not only addresses emotional and physical well-being but also strengthens the spiritual connection with the Creator, making it a safe, practical, and comprehensive option in alternative healing methods.